Influence of Climate on Radial Growth of Holm Oaks (Quercus Ilex Subsp. Ballota Desf) from SW Spain - Patón, Daniel; García-Herrera, Ricardo; Cuenca, Javier; Galavis, Mamen; Roig, Fidel (Geochronometria, 2009)
A total of 47 trunk sections from Holm Oak (Quercus ilex subsp. ballota Desf) trees growing at two different sites at the Extremadura region (SW Spain) were considered in the computation of a regional tree-ring chronology useful to interpret the tree-ring/Mediterranean climate relationships. This is the first dendroclimatological research of Holm Oaks conducted to reveal its potential use as a climatic proxy. The obtained tree-ring chronologies were compared with climatic parameters based on monthly, seasonal and annual rainfall, and monthly maximum, minimum and average temperature. The best correlations were obtained with maximum temperatures during the period between previous winter and early spring. Influence of rainfall was less relevant. Growth of this species indicates a typical bimodal (spring and autumn) strategy that avoids low winter temperatures and summer drought. Despite some technical difficulties recognizing tree rings in Holm Oaks, its good sensitivity to climate variability and its wide distribution and longevity (~800 years), allow us to consider this species as a good candidate for temperature reconstructions in the Mediterranean Basin.
Keywords: climatic change; Dendrochronology; dendroclimatology; Extremadura; maximum temperature; Quercus ilex; Spain; tree rings

Influence of Climate on Radial Growth of Holm Oaks (Quercus Ilex Subsp. Ballota Desf) from SW Spain - Patón, Daniel; García-Herrera, Ricardo; Cuenca, Javier; Galavis, Mamen; Roig, Fidel (Geochronometria, 2009)
A total of 47 trunk sections from Holm Oak (Quercus ilex subsp. ballota Desf) trees growing at two different sites at the Extremadura region (SW Spain) were considered in the computation of a regional tree-ring chronology useful to interpret the tree-ring/Mediterranean climate relationships. This is the first dendroclimatological research of Holm Oaks conducted to reveal its potential use as a climatic proxy. The obtained tree-ring chronologies were compared with climatic parameters based on monthly, seasonal and annual rainfall, and monthly maximum, minimum and average temperature. The best correlations were obtained with maximum temperatures during the period between previous winter and early spring. Influence of rainfall was less relevant. Growth of this species indicates a typical bimodal (spring and autumn) strategy that avoids low winter temperatures and summer drought. Despite some technical difficulties recognizing tree rings in Holm Oaks, its good sensitivity to climate variability and its wide distribution and longevity (~800 years), allow us to consider this species as a good candidate for temperature reconstructions in the Mediterranean Basin.
Keywords: climatic change; Dendrochronology; dendroclimatology; Extremadura; maximum temperature; Quercus ilex; Spain; tree rings

Cork oak (Quercus suber L.) wood growth and vessel characteristics variations in relation to climate and cork harvesting - Leal, Sofia; Nunes, Elsa; Pereira, Helena (European Journal of Forest Research, 2007)
Variations in tree ring growth of Quercus suber L. were analysed using dendrochronological techniques on cork oak discs from trees harvested in the cork producing region of Alentejo, Portugal. A tree-ring chronology containing a strong common signal and covering the period from 1970 to 1995 was build for ca. 30-year-old cork oaks never submitted to cork harvesting using 14 trees that crossdated satisfactorily out of 30 sampled trees. The tree ring indices correlated positively with September temperature (r = 0.48, P < 0.05) and very strongly with precipitation totals from previous October until current February (r = 0.82, P < 0.001) showing that the water stored in the soil during the autumn and winter months prior to the growing season has a primordial effect on the growth of the given season. The effects of cork harvesting were analysed by comparing mean ring width, mean annual vessel area, vessel density (nvessels/mm 2 ), and vessel coverage (percentage of transverse surface occupied by vessels) between three mature cork oak trees and three young trees, for the period from 1987 to 1996, corresponding to the growth between two consecutive cork removals in the case of mature trees. In 1988, 1989 and 1996 (corresponding to the ﬁrst and second years after cork removal, and 1996 to a year of cork removal), the ratios between ring widths of young versus mature trees was twice that for the rest of the period. However, an effect of cork removal indicated by eventual alterations in vessel size and distribution in the wood rings corresponding to the years 1988, 1989 and 1996 in the mature cork oaks was not observed.
Keywords: cork harvesting; Dendrochronology; Precipitation; Quercus Suber L; tree rings; wood anatomy; wood vessels

Comparative stem-growth rates of Mediterranean trees under background and naturally enhanced ambient CO2 concentrations - Tognetti, Roberto; Cherubini, Paolo; Innes, John L (New Phytologist, 2000)
Ring widths of five Mediterranean forest tree species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Quercus ilex and Quercus pubescens) growing close to a natural source of CO2 in Tuscany, Italy and at a nearby control site were compared. At the CO2-enriched site, trees have been growing for decades under elevated CO2 concentrations. They originated from parent trees that also grew under elevated CO2 in natural conditions, and they have been continuously exposed to elevated CO2 throughout their growth. Tree-ring series from each of the species were prepared. Assigning calendar dates to rings was difficult but possible, and ring-width series were built for all species. The ring-width data were analysed using a two-sided t-test to assess if there was a difference between the radial growth at the CO2-enriched site and the control site. The cumulative basal area at the same cambial age at both sites was also compared using a Wilcoxon test. Radial growth of trees at the CO2-enriched site was not significantly different from growth at the control site. For each species, year by year, radial growth at the CO2-enriched site was tested against the control site and significant differences were found in only a few years; these differences were not synchronous with extreme climatic events. The expected increase in above-ground productivity, as one of the ecosystem responses to increasing CO2 during drought stress, was not observed in this Mediterranean woody plant community, despite being water-limited. Other resource limitations, such as low nutrient availability (common in the Mediterranean region), may have counteracted the positive effect of elevated CO2 under drought stress, or trees may have acclimated to the high CO2.
Keywords: Arbutus unedo (strawberry tree); Carbon Sequestration; Dendroecology; Mediterranean trees; natural CO2 springs; Quercus ilex (holm oak); tree rings; water stress

Comparative stem-growth rates of Mediterranean trees under background and naturally enhanced ambient CO2 concentrations - Tognetti, Roberto; Cherubini, Paolo; INNES, JOHN L. (New Phytologist, 2000)
Ring widths of five Mediterranean forest tree species (Arbutus unedo, Fraxinus ornus, Quercus cerris, Quercus ilex and Quercus pubescens) growing close to a natural source of CO2 in Tuscany, Italy and at a nearby control site were compared. At the CO2-enriched site, trees have been growing for decades under elevated CO2 concentrations. They originated from parent trees that also grew under elevated CO2 in natural conditions, and they have been continuously exposed to elevated CO2 throughout their growth. Tree-ring series from each of the species were prepared. Assigning calendar dates to rings was difficult but possible, and ring-width series were built for all species. The ring-width data were analysed using a two-sided t-test to assess if there was a difference between the radial growth at the CO2-enriched site and the control site. The cumulative basal area at the same cambial age at both sites was also compared using a Wilcoxon test. Radial growth of trees at the CO2-enriched site was not significantly different from growth at the control site. For each species, year by year, radial growth at the CO2-enriched site was tested against the control site and significant differences were found in only a few years; these differences were not synchronous with extreme climatic events. The expected increase in above-ground productivity, as one of the ecosystem responses to increasing CO2 during drought stress, was not observed in this Mediterranean woody plant community, despite being water-limited. Other resource limitations, such as low nutrient availability (common in the Mediterranean region), may have counteracted the positive effect of elevated CO2 under drought stress, or trees may have acclimated to the high CO2.
The following values have no corresponding Zotero field: publisher: Cambridge University Press
Keywords: Arbutus unedo (strawberry tree); Carbon Sequestration; Dendroecology; Mediterranean trees; natural CO2 springs; Quercus ilex (holm oak); tree rings; water stress

Radial distribution of Ni in stemwood of Quercus ilex L. trees grown on serpentine and sandy loam (umbric leptosol) soils of NE-Portugal - Nabais, C; Freitas, H; Hagemeyer, J; Breckle, S W (Plant and soil, 1996)
Concentrations of Ni were determined in xylem and phloem of Quercus ilex trees growing on serpentine and sandy loam soils of northeast Portugal. Radial distribution patterns of Ni in stemwood were compared to variations in annual growth increments of the trees. Concentrations of Ni in xylem and phloem were higher in Q. ilex from serpentine soil, when compared with Q. ilex of a sandy loam soil. The radial distributions of Ni showed large variations among the trees, although they all grew in the same area within a short distance from each other. These differences can be caused by small-scale spatial variations in the soil. Therefore, the use of such radial Ni distributions for a retrospective biomonitoring of the Ni pollution of larger areas appears questionable.
Keywords: dendrochemistry; Nickel; Quercus ilex; serpentine; tree rings